Multi-objective design optimization of a high performance disk brake using lichtenberg algorithm - Pereira, João Luiz Junho; Guedes, Felipe Ciolini; Francisco, Matheus Brendon; Chiarello, André Garcia; Gomes, Guilherme Ferreira (Mechanics based design of structures and machines, 2024)
Purpose: This work is dedicated to disk brake rotor optimization using parametric and topological optimizations considering three conflicting objectives: mass, temperature variation, and breaking time. The rotor had explicit equations modeled and the Multi-objective Lichtenberg Algorithm (MOLA), which is executable in Matlab®, performed a parametric optimization to find the general rotor design parameters. Several optimization techniques have been developed last few years, however, the ones that have presented better results are meta-heuristics associated with posteriori decision-making techniques. Thus, in this work, this powerful and recently created multi-objective meta-heuristic was applied. The MOLA found more than 3000 solutions and the TOPSIS was used for decision-making. Then, the rotor was designed in the SolidWorks® 3D software and the ANSYS software was applied to perform topological optimization, where more mass was removed and analysis regarding the work stresses was done. To the best author's knowledge, this is the first work to consider multi-objective parametric and topological optimization for this structure at the same time in the literature. A considerable mass reduction was obtained. It was possible to find a rotor weighing only 164.8 g with the lowest safety factor across the entire rotor equals 2.02. Therefore, a rotor optimized with reliable, lightweight, and that allows a low braking time was found. Also, these results show that the methodology used can be applied in other structures with complex parameterization.